Morphine for elective endotracheal intubation in neonates: a randomized trial [ISRCTN43546373] - Gray Shari; Kalyn Angela; Doucette Joanne; Lemyre Brigitte; Marrin Michael L (BMC, 2004)
Abstract Background Elective endotracheal intubations are still commonly performed without premedication in many institutions. The hypothesis tested in this study was that morphine given prior to elective intubations in neonates would decrease fluctuations in vital signs, shorten the duration of intubation and reduce the number of attempts. Methods From December 1999 to September 2000, infants of all gestations admitted to a level III neonatal intensive care unit and requiring an elective endotracheal intubation were randomly assigned to receive morphine 0.2 mg/kg IV or placebo 5 minutes before intubation. Duration of severe hypoxemia (HR< 90/min and Sp02<85%), duration of procedure, duration of hypoxemia (Sp02<85%), number of attempts and change in mean blood pressure were compared between groups. Results 34 infants (median 989 g and 28 weeks gestation) were included. The duration of severe hypoxemia was similar between groups. Duration of procedure, duration of hypoxemia, number of attempts and increases in mean blood pressure were also similar between groups. 94% of infants experienced bradycardia during the procedure. Conclusion We failed to demonstrate the effectiveness of morphine in reducing the physiological instability or time needed to perform elective intubations. Alternatives, perhaps with more rapid onset of action, should be considered.